Physical Properties and Interaction With the Ocular Surface of Water-Gradient Contact Lenses. Issue 4 (22nd April 2023) - Ponzini, Erika; Recchioni, Alberto; Cheloni, Riccardo; Zeri, Fabrizio; Tavazzi, Silvia
Abstract: Since the introduction of silicone hydrogel contact lenses, many silicone-hydrogel materials have been produced, including water-gradient contact lenses with a silicone hydrogel core and a thin hydrogel outer layer (e.g., delefilcon A, verofilcon A, and lehfilcon A). Their properties have been investigated in various studies assessing both the chemical–physical characteristics and the comfort, but the overall picture is not always consistent. In this study, water-gradient technology is reviewed by looking at basic physical properties both in vitro and in vivo and at the interaction with the human ocular surface. Surface and bulk dehydration, surface wetting and dewetting, shear stress, interaction with tear components and with other environmental compounds, and comfort are discussed.